Impact of light intensity and quality on chromatophore and nuclear gene expression in Paulinella chromatophora, an amoeba with nascent photosynthetic organelles. (22nd March 2017) - Zhang, Ru; Nowack, Eva C. M.; Price, Dana C.; Bhattacharya, Debashish; Grossman, Arthur R.
Summary: Plastid evolution has been attributed to a single primary endosymbiotic event that occurred about 1.6 billion years ago (BYA) in which a cyanobacterium was engulfed and retained by a eukaryotic cell, although early steps in plastid integration are poorly understood. The photosynthetic amoeba Paulinella chromatophora represents a unique model for the study of plastid evolution because it contains cyanobacterium‐derived photosynthetic organelles termed 'chromatophores' that originated relatively recently (0.09–0.14 BYA). The chromatophore genome is about a third the size of the genome of closely related cyanobacteria, but 10‐fold larger than most plastid genomes. Several genes have been transferred from the chromatophore genome to the host nuclear genome through endosymbiotic gene transfer (EGT). Some EGT‐derived proteins could be imported into chromatophores for function. Two photosynthesis‐related genes ( psaI and csos4A ) are encoded by both the nuclear and chromatophore genomes, suggesting that EGT in Paulinella chromatophora is ongoing. Many EGT‐derived genes encode proteins that function in photosynthesis and photoprotection, including an expanded family of high‐light‐inducible (ncHLI) proteins. Cyanobacterial hli genes are high‐light induced and required for cell viability under excess light. We examined the impact of light on Paulinella chromatophora and found that this organism is light sensitive and lacks light‐induced transcriptional regulation of chromatophore genes and most EGT‐derived nuclear genes. However, several nc HLI genes have reestablished light‐dependent regulation, which appears analogous to what is observed in cyanobacteria. We postulate that expansion of the nc HLI gene family and its regulation may reflect the light/oxidative stress experienced by Paulinella chromatophora as a consequence of the as yet incomplete integration of host and chromatophore metabolisms. Significance Statement: The amoeba Paulinella chromatophora has photosynthetic organelles that originated from a recent primary endosymbiosis, and thus studying it provides an opportunity to investigate early events in plastid evolution. Here we elucidate how its gene expression is regulated by light, providing fundamental insights into how an oxygen‐producing photosynthetic organelle is established.